JOURNAL OF GOVERNMENT & POLITICS : Managing Ethics in Public Sector : Integrity Approaches - Songklin Prayote (FISIPOL UMY, 2016)
There are two main approaches of ethics, integrity and compliance approach, applying in public administration.